Analisis Yuridis Terhadap Penegakan Hukum Kasus Pelecehan Seksual Oleh Tenaga Medis Di Indonesia - Sakti Musa Jafar; Wahyudi, Wahyudi (Dialog Legal: Jurnal Syariah, Jurisprudensi dan Tata Negara, 2025)
Sexual harassment perpetrated by medical personnel constitutes a serious violation of human rights and medical professional ethics. This study aims to analyze the juridical aspects of law enforcement in cases of sexual harassment by medical personnel in Indonesia, with a particular focus on the implementation of Law Number 12 of 2022 concerning the Crime of Sexual Violence. The research employs a normative juridical approach, utilizing document studies of legislation, court decisions and literature. The findings indicate that while regulations provide for strict criminal sanctions, the enforcement of these laws still faces various obstacles, such as underreporting by victims and difficulties in securing strong evidence. Consequently, efforts are needed to enhance public awareness and optimize the capacity of law enforcement agencies in addressing these cases to ensure that justice is effectively served. This research offers strategic recommendations for policymakers and legal practitioners to strengthen the protection of sexual harassment victims within the healthcare environment.